2014
DOI: 10.1177/1049732314529667
|View full text |Cite
|
Sign up to set email alerts
|

Blame, Shame, and Lack of Support

Abstract: In this research, we examined the experiences of individuals living with obesity, the perceptions of health care providers, and the role of social, institutional, and political structures in the management of obesity. We used feminist poststructuralism as the guiding methodology because it questions everyday practices that many of us take for granted. We identified three key themes across the three participant groups: blame as a devastating relation of power, tensions in obesity management and prevention, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
67
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 31 publications
8
67
1
3
Order By: Relevance
“…Similar 'choice-promoting' discourses found in the obesity literature (i.e., 'eat less, move more') are argued to induce feelings of shame and proportion blame (Kirk et al, 2014). The role of individual responsibility in the pursuit of physical fitness was further emphasised in constructions of fitness as a battle against the self (Theme 5) which implies that one's sense of self-worth can be derived from exercise participation (Ryan & Deci, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Similar 'choice-promoting' discourses found in the obesity literature (i.e., 'eat less, move more') are argued to induce feelings of shame and proportion blame (Kirk et al, 2014). The role of individual responsibility in the pursuit of physical fitness was further emphasised in constructions of fitness as a battle against the self (Theme 5) which implies that one's sense of self-worth can be derived from exercise participation (Ryan & Deci, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…This research is especially troubling given that biased attitudes toward weight may impact a patient's quality of care in the health system (Kirk et al, 2014;Waller et al, 2012). Mold and Forbes (2013) found that health professionals have negative attitudes toward patients with obesity, spend less time with patients with obesity, and offer them fewer treatment options.…”
mentioning
confidence: 99%
“…Recent surveys of health professionals have found that most feel unprepared to care for patients with obesity, lack adequate referral sources, and would support additional training that would lead to the improved care of individuals with obesity (Bleich et al, 2012;Kirk et al, 2014). This research also suggests that health professionals are frustrated by conflicting messages about the nature of obesity, experience difficulty in understanding the complexity of obesity, and feel unsupported by the health care system, which often results in frustration and disappointment being placed on the patients themselves (Kirk et al, 2014).…”
mentioning
confidence: 99%
“…[6][7][8] Specifically, the current public health obesity narrative promotes assumptions about personal irresponsibility and lack of willpower among people with obesity. 9 These assumptions contribute to the beliefs that people with obesity and their children lack awareness and knowledge about healthy eating and physical activity and are to blame for the obesity epidemic. 10 There is extensive research demonstrating the negative effects of weight bias.…”
mentioning
confidence: 99%
“…Individuals experience shame and frustration for not being able to implement lifestyle change recommendations. 9 We also know that the public negatively perceives strategies that imply personal responsibility for obesity. 37 Furthermore, individuals who feel stigmatized for their weight may engage in unhealthy behaviours and dangerous weight loss practices, impacting their health even more negatively.…”
mentioning
confidence: 99%